Structural, dielectric and impedance spectroscopy studies in (Bi0.90R0.10)Fe0.95Sc0.05O3 [R = La, Nd] ceramics - Coondoo, Indrani
Polycrystalline BiFeO3 and Bi0.90R0.10)Fe0.95Sc0.05O3 [R=La, Nd] ceramics were synthesized by solid-state reaction method. XRD studies confirmed the formation of single-phase compositions. The particle sizes obtained from XRD data were 43, 31 and 30 nm for BFO, BLFSO and BNFSO, respectively. Dielectric studies revealed anomalies around 200 degrees C and near the Neel temperature. The latter is attributed to the phase transition as an influence of vanishing magnetic order on the electric order usually observed in magneto-electric ordered systems. Complex impedance spectroscopy (CIS) technique was utilized to investigate the intra- and inter-granular contributions to the impedance in the studied compositions as a function of temperature and frequency. CIS studies revealed that the electrical relaxation process was temperature dependent and non-Debye type. AC conductivity studies revealed that conductivity in samples was mainly due to the hopping of oxygen vacancy between the oxidation states (Fe3+/Fe2+) of iron. (C) 2014 Elsevier Ltd and Techna Group S.r.l. All rights reserved.